1985
DOI: 10.21608/asat.1985.26588
|View full text |Cite
|
Sign up to set email alerts
|

THE OPTIMUM WIDTH FOR LHL-GaAs-IMPATT DIODES

Abstract: In this paper the results of an extensive study of the effects of the drift region width on the performance of LHL-GaAs-IMPATT diodes are presented. These results have been obtained using an IMPATT-diode full scale computer simulation program. It is demonstrated that the transition between the regular IMPATT mode and the high-efficiency modes becomes more abrupt as the drift region width is increased. It is also found that when the diode operates according to the highefficiency modes the efficiency is not a se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1999
1999
1999
1999

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Since these effects are inherent in InP material, it is only possible to improve the performance of p-type InP IMPATTs through modifying the microwave circuit where the diode is imbedded. Since it has been previously reported that the performance of IMPATTs could be improved if it is driven by a nonsinusoidal voltage waveform [4][5][6][7], the external circuit attached to the diode must be capable of supporting such waveforms. However, no comprehensive study has been conducted for determining the optimum waveform.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since these effects are inherent in InP material, it is only possible to improve the performance of p-type InP IMPATTs through modifying the microwave circuit where the diode is imbedded. Since it has been previously reported that the performance of IMPATTs could be improved if it is driven by a nonsinusoidal voltage waveform [4][5][6][7], the external circuit attached to the diode must be capable of supporting such waveforms. However, no comprehensive study has been conducted for determining the optimum waveform.…”
Section: Introductionmentioning
confidence: 99%
“…A special waveform is proposed to be the optimum waveform for p-type InP IMPATT. This proposition is supported by an extensive investigation of IMPATT operation [1][2][3][7][8]. This investigation has been conducted using a modified version of the full-scale computer simulation program described elsewhere [8].…”
Section: Introductionmentioning
confidence: 99%